Odpowiedzi

2009-12-17T16:54:06+01:00
Uzupełnij zapis :
b) 2x+y=7
5x-2y=4

y=7-2x
5x-14+4x=4

d)
5x+2y=7
3x-6y=5

2y=7-5x
3x-147+210x-75x²=5
2009-12-17T16:54:16+01:00
B)
2x+y=7
5x-2y=4

y=7-2x
5x-2*(7-2x)=4

d)
5x+2y=7
3x-6y=5

2y=7-5x
3x-6*2*(7-5x)=3x-12*(7-5x)=5
2009-12-17T17:10:23+01:00

b) 2x+y=7
5x-2y=4

y=-2x+7
5x=2y+4
5x=2(2x+7)+4
5x=4x+14+4
x=18
2x+y=7
2*18+y=7
y=-36+7
y=-29

d)
5x+2y=7
3x-6y=5

2y=-5x+7
3x=5 +6y
y=-2,5x+3,5
3x=5+6(-2,5x+3,5)
3x=5-15x+21
18x=26
x=1,4
y=-2,5x+3,5
y=-2,5*1,4+3,5
y=0